Optimizing Pain and Rehabilitation After Knee Arthroplasty: A Two-Center, Randomized Trial. (November 2016) - Choi, Stephen; O'Hare, Turlough; Gollish, Jeffrey; Paul, James E.; Kreder, Hans; Thorpe, Kevin E.; Katz, Joel D.; Mamdani, Muhammad; Moisiuk, Peter; McCartney, Colin J.
Abstract : BACKGROUND: This randomized trial compared (1) continuous femoral nerve block (cFNB), (2) single femoral nerve block (sFNB), and (3) local infiltration analgesia (LIA) with respect to analgesic and functional outcomes after primary tricompartmental knee arthroplasty (TKA). METHODS: One hundred twenty patients undergoing primary tricompartmental knee arthroplasty were randomly assigned to 1 of 3 interventions for postoperative analgesia: (1) cFNB—preoperative bolus of ropivacaine 0.5% 20 mL followed by ropivacaine 0.2% 5 mL per hour for 48 hours; (2) sFNB—preoperative bolus of ropivacaine 0.5% 20 mL with placebo 0.9% saline 5 mL per hour for 48 hours; or (3) LIA—intraoperative tricompartmental injection of ropivacaine 0.2% (150 mL) with epinephrine (10 µg/mL) and ketorolac 30 mg with femoral placebo 0.9% saline 20 mL preoperative bolus and 0.9% saline placebo 5 mL per hour for 48 hours. All participants received an identical, standardized, postoperative multimodal analgesic regimen. Participants, health care providers, data collectors, and analysts were blinded. All participants received identical perineural catheters and perineural/LIA solution (depending on randomized intervention) to maintain blinding. The primary outcome measure was numeric rating scale for pain (NRS) during physiotherapy on postoperative day (POD) 2 at 9:00 AM. Secondary outcomes included opioid consumption, NRS on POD 1 (rest/physiotherapy/worst), functional outcomes, and block complications. RESULTS: For the primary outcome, pain during physiotherapy on POD 2 at 9:00 AM, the overall analysis of covariance (ANCOVA) was significant ( P = .049), but pairwise comparisons did not demonstrate any significant differences between treatment arms. NRS was 4.6 (95% confidence interval [CI], 3.3–6.0) for the cFNB group, 4.6 (95% CI, 3.3–6.0) for the sFNB group, and 3.4 (95% CI, 2.2–4.8) for the LIA group. The following is the mean difference in NRS on POD 2 at 9:00 AM among groups: cFNB−LIA (1.2, 95% CI, −0.1 to 2.5; P = .073); sFNB−LIA (1.2, 95% CI, −0.2 to 2.5; P = .097); cFNB−sFNB (0.0, 95% CI, −1.3 to 1.4; P = .996). There were no statistically significant differences between groups in cumulative 48-hour opioid consumption or functional outcomes. cFNB and LIA were superior to sFNB for NRS on POD 1 for worst pain experienced and pain during physiotherapy, respectively. There were no adverse events associated with study procedures reported among participants in the 3 groups. CONCLUSIONS: Our findings suggest no clinically significant differences between cFNB, LIA, and sFNB for pain during physiotherapy on POD 2 after TKA. Secondary analyses suggest that cFNB and LIA are superior to sFNB for early analgesic outcomes (NRS on POD 1) after TKA.